Profitability determining factors of banking sector: Panel data analysis of commercial banks in South Asian countries - Yuan, Deli; Gazi, Md. Abu Issa; Harymawan, Iman; Dhar, Bablu Kumar; Hossain, Abu Ishaque (Frontiers in Psychology, 2022)
Aim of the article The main purpose of this article was to investigate the impact of the determinants of profitability on the commercial banks in Asian countries. An Asian country like Bangladesh and India was selected as the research field. The present study also pursues to examine the impact of specific factors and macroeconomic factors on the profitability in the Bangladeshi and Indian private commercial banking sectors. Methods applied and analysis tools The data were retrieved from the Annual Reports of Indian and Bangladeshi private commercial banks covering the period of 2010–2021. As sample, 40 private commercial banks were considered randomly, of which 20 were from India and 20 were from Bangladesh. The panel data research methodology was used as an estimation technique to analyze the data. Also, the ordinary least squares (OLS) regression model was used to scrutinize data. To check whether the models were appropriate, the Breusch–Pagan Lagrange Multiplier (LM) Test was employed. Banks' specific factors and microeconomic factors showed almost the same variations for both Bangladesh's and India's private banks. All models and tests were evaluated using E-views econometric software. The major findings The present study finds that the Return on Asset (ROA) from the banks' specific variables, strength of the Bank size (BS), and Debt to Asset Ratio (DAR) are found to be positive and significant. For banks, the Deposit to Asset Ratio (DTAR) and the Loan to Deposit Ratio (LDR) are found to be negative and significant. The Equity to Asset Ratio (EAR) and Debt to Equity Ratio (DER) do not have any positive/negative impact. Contribution, originality, and implications As macroeconomic variables, the inflation rate (IR) and the GDP growth rate (GDPGR) are measured and found to be positive and significant for ROA. As macroeconomic variables, the Inflation Rate (IR) and the GDP Growth Rate (GDPGR) are found to be positive and significant in the case of ROA. The concerned authorities responsible for regulating the financial performance of the banking sector can use the results of this study to take various fruitful decisions on bank profitability.